Ion-pair recognition by a ditopic calix[4] semitube receptor - Webber, P; Beer, P (2003)
A ditopic receptor comprised of a calix[4]semitube for cation recognition and urea functionality for anion complexation has been developed. This receptor displays a remarkable selectivity and fast kinetics of complexation for potassium cation over all other Group 1 metal cations, a property mirroring that of the parent calix[4]semitube 1. 1H NMR studies reveal that 4 cooperatively binds a range of sodium and potassium halide and acetate salts in 2 : 1 CDCl3 : CD3CN, with anion binding enhancements of over thirty-fold in the case of bromide. Extraction experiments demonstrated that the host could solubilise sodium and potassium salts in chloroform. © The Royal Society of Chemistry 2003.